Penyerapan Informasi Masyarakat Terhadap Media Informasi Dinas Kominfo Kota Batam Studi Kasus Pembuatan Kartu Pencari Kerja Online - Suci Tria Setianingsih; Nelmiawati Nelmiawati (Politeknik Negeri Batam, 2020)
The vision of Diskominfo Batam City is “Realization of governance and public service ICT-based integrated and aasily accessible public.” To find out if media used Diskominfo Batam City facilitate the absorption of public information, it is necessary to test to the media with testing before and after disclosed media information. Using quantitative research design and survey, this research was conducted against 60 respondents (30 respondents video testing and 30 respondents web testing) at productive age work. Data collection in this research using test to respondents in the from of 10 questions before and after showing the media. Data processing using the application IBM SPSS Statistics Subscription Preview to Shapiro-Wilk Test, Paired Sample T-Test and Wilcoxon Signed Rank Test. Result 0.0075 < 0.025 on Paired Sample T-Test for video testing and 0.001 < 0.05 on Wilcoxon Signed Rank Test for website testing. But researchers did not find significant distinction on the results, and assumed that the cause is a little more questions and less profound material make information obtained less varied.